ASPEK MOTIVASI HIDUP DALAM NOVEL “ANAK RANTAU” KARYA AHMAD FUADI - Ike Tri Pebrianti; Meldah Novitasari (Balai Bahasa Sumatera Utara, 2022)
This study aims to describe the motivational aspects of life in Ahmad Fuadi's novel